Rerative Risk of Management Factors which Influence Infertility of Artificial Insemination in Bali Cattle in East Lombok - Rosyidi, Anwar; Dradjat, Adji Santoso; Zainuri, Lalu Ahmad; Wirapribadi, Lalu; Binetra, Tjok. Suwendra; Haryanto, Haryanto (Jurnal Veteriner; Vol 22 No 2 (2021)DO - 10.19087/jveteriner.2021.22.2.292, 2021)
The aim of this study was to evaluate odds ratio (OR) of management factors on infertility of artificial insemination results. Three traditional farmer groups were purposively choosed, based on percentage of calf born of AI program. Group I, with calves born of 61.22%, Group II with calves born of 38,89 %, and group III with calves born of 30,0%. The management factors evaluated were 1. ownerships of cattle, 2. raise cattle in separate pen with other, 3. cattle raised in pen dirty pen, 4. not enough feed given 5. body condition score. The data was obtained by dichotomy questioner and observation then evaluated using odds ratio (OR), when OR more than 1 indicated the high risk of factor to infertility. The results of OR in Group I showed that ownership (1,18), separated pen (0,54), dirty pen (2,11), less feed (3,20) and body condition (0,22). The results in Group II showed that ownership (0,83) , separated pen (1,12), dirty pen (0,14), less feed (2,08) and body condition (2,00). The results of odds ratios in Group III showed that ownership (1,63), separated pen (3,83), dirty pen (0,88), less feed (1,00) and body condition (0,12). These data indicated that ownerships, dirty pen, less feed and body condition were factors which may confounding with other factors. However less OR of separate pen were, in Group I (0,54), Group II (1,12) and Group III (3,83) consistently with number of calves produced. It can be concluded that separate pen was a factor which influence calves produced in using artificial insemination.